The relation of the nutritional composition of TMR and the urea concentration in milk for evaluation nutrition and efficiency of protein utilization in lactating dairy cows - Maskaľová, Iveta; Vajda, Vladimír; Timkovičová Lacková, Petra (Animal Welfare, Etológia és Tartástechnológia (AWETH), 2020)
In order to diagnose of protein nutrition of dairy cows in the first lactation phase, were used the analysis milk urea nitrogen (MUN) as the average per production group and individual cows in the group. The aim of this study was to evaluate the nutritional and production factors that affect the MUN and the relationships between MUN, the efficiency of nitrogen utilisation from feed into milk, and the ecological burden via excretion of urea nitrogen in urine. The evaluation of the production parameters of dairy cows together on 30 farms in total in 3 150 dairy cows was carried out according to the individual evaluations of the production carried out by the Plemenárska služba SR š.p. The analysed relations evaluated by linear, or by multiple stepwise regression confirmed the crude protein (CP) as the best single marker for the estimation of MUN and included the proportion of the total tolerance of 0.693 expressed regression equation [MUN (mg/dl) = -13.2 + 0.16 x CP (g/kg dry matter)]. For mixed models, the rate of variation expressed by this relationship increased to 0.720 (P<0.0001) for nutrient concentration and 0.783 for nutrient intake (P<0.0001). The relationship between MUN and the evaluated nutrients was closer when nutrient concentration in TMR was used, rather than daily intake of nutrients. MUN had a positive relationship to CP and neutral detergent fibre (NDF) and the negative relationship was confirmed with NEL and non-fibrous carbohydrates (NFC) and NFC/CP, NEL/CP and NDF/CP in TMR.